Software developer competency framework - Minani, David Muhangwa (Cape Peninsula University of Technology, 2013)
The application of software systems in business organizations continue to increase as the Internet technology grows. Business processes that previously required manual interventions are becoming automated using software systems. The use of software systems is fundamental to electronic processing of business transactions. More business organizations, large and small, are utilizing information technology in order to have competitive advantage in the business arena. Software is ubiquitous. Among areas where software plays core roles are e-Banking where software systems are used to process banking transactions, e-Health where software systems are used to facilitate activities in the health sector, e-Commerce where software systems are used to facilitate online business transactions, e-Government where software system are used to facilitate government activities and e-Learning where software systems are used to facilitate the teaching and learning process. Nevertheless, the large number of failing software projects and the increase in software security problems coupled with shortage of skilled software developers are still major obstacles in the software development industry. Among others, the solution can be achieved by improving the competency of software developers so that software systems developed are of good quality, safe, robust, and support business objectives. Software companies and business organizations stand a big chance to increase their return on investment (ROI), if competencies of software developers are improved. A software developer plays critical roles in software development projects. A software developer, however, requires specific skills and knowledge in order to develop software systems that solve problems and deliver solutions. This research is about competencies of software developers. The research focuses on software development activities performed by software companies and business organizations within the Western Cape Province. The unit of analysis is software developers. Data pertaining to tasks performed by software developers, tools used by software developers and skills required were collected, examined and analysed. The objective of the research is to develop a competency framework for software developers. It can be used by institutions and the industry to provide better education. Most importantly, the industry will have access to competent software developers who can perform their job well. As justified in this research, knowledge of a competency framework for software developers is extremely essential.ÿ
Thesis (MTech (Information Technology))--Cape Peninsula University of Technology, 2013
Keywords: Computer software -- Development; Computer software industry; Dissertations, Academic; MTech